Antimicrobial peptide AMP-17 induces protection against systemic candidiasis and interacts synergistically with fluconazole against Candida albicans biofilm - Sun, Chaoqin; Zhu, Lijuan; Yang, Longbing; Tian, Zhuqing; Jiao, Zhenlong; Huang, Mingjiao; Peng, Jian; Guo, Guo (Frontiers in Microbiology, 2024)
Candida albicans, a common commensal and opportunistic fungal pathogen in humans, can occasionally progress to disseminated candidiasis which is a serious condition with a high morbidity and fatality rate. The emergence of drug-resistant fungal strains compels us to look for an efficient treatment solution. Our earlier studies have demonstrated that the unique antimicrobial peptide AMP-17 from Musca domestica has a strong antifungal impact on C. albicans in vitro. Here, we verified the therapeutic effects of AMP-17 on systemic candidiasis in vivo and the peptide interacts with fluconazole, a common antifungal medication, to treat systemic candidiasis. In the disseminated candidiasis model of Galleria mellonella and mice challenged with C. albicans, AMP-17 increased the survival rates of infected larvae and mice to 66.7 and 75%, respectively. Furthermore, the peptide lowered the load of C. albicans in the infected larvae and the kidneys of the mice by nearly 90%. Additional histological examination and measurements of plasma cytokines showed that the injection of AMP-17 markedly reduced the inflammatory response and balanced cytokine expression. Furthermore, checkerboard micro dilution experiments demonstrated that AMP-17 and fluconazole worked in synergy to inhibit C. albicans in the biofilm mode. According to morphological studies, AMP-17 and fluconazole together decreased the production of hyphae throughout the C. albicans biofilm formation process, loosening the mature biofilms’ structure and lowering the amount of carbohydrates in the extracellular matrix (ECM) of the biofilms. Taken together, these results showed that AMP-17 would be a viable treatment for systemic candidiasis and might be a different approach to combating Candida biofilm, either by itself or in conjunction with fluconazole.